The relationship between board characteristics and firm financial performance in Malaysia - Sin, Huei Ng; Boon, Heng Teh; Tze, San Ong; Wei, Ni Soh (Virtus Interpress, 2016)
Corporate governance has drawn attention of investors and government after the incidence of financial crisis world- wide since the late 90’s. Despite that reforms of corporate governance have been in place in Malaysia, voluntary disclosure of corporate governance has yet to proof its impact on the financial performance of the companies. This study examines the relationship between corporate governance attributes and firm financial performance in Malaysia. The relationship between board characteristics (board tenure, board size and CEO duality) were analyzed to investigate their correlation with firm financial performances. A total of 100 public listed companies were randomly selected from Bursa Malaysia for the year 2009 to 2013. Random effect panel data regression was obtained by using Stata. This study finds that board size, board tenure were significant to Return on Equity (ROE) and Return on Assets (ROA). However, firm size has no significant relationship with firm financial performance. It is recommended that apart from including more variables as controlling effects on firm financial performance and examining few industries as sample, it is also good to examine the correlation between board characteristics and corporate governance variables (foreign listings, equity analysis, external auditors, leverage ratios, dividend policy, etc.) on one hand, and ownership structures on the other hand, that have significant impact on firm financial performance.